2023
DOI: 10.1108/lht-06-2021-0194
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the role of ICT in bridging the digital divide: a transitional analytical framework for ICT access to impact

Abstract: PurposeIn light of the shift in focus from information communication technology (ICT) access (access divide) and skills (skills divide) to the tangible impacts of ICT use (impact divide), a growing number of scholars have called for further investigation into the inter-territorial and multi-dimensional aspects of the digital divide in China. This study aims to address these gaps by examining the disparities across 31 provinces, particularly emphasizing the transition from the traditional access and skills divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The advent of ICTs like mobile applications has accelerated the speed at which information proliferates (Ozor and Toner, 2022;Le, 2023). Studies have further confirmed that ICTs stimulate cognitive and innovative behavior but also streamlines processes which fosters the ability to process and share more information for decision-making (Kravchenko, 2021;Munir and Beh, 2019;Harju et al, 2023;Hussain et al, 2023). In the agriculture sector, basic ICTs like mobile phones and televisions have bridged the information gaps created by the inaccessibility of extension workers and prevalent costs associated with reaching out to official government outreach centres (Byamukama et al, 2022;Subramanian, Bozzola and Nugent, 2022;Ravindra et al, 2020).…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 99%
“…The advent of ICTs like mobile applications has accelerated the speed at which information proliferates (Ozor and Toner, 2022;Le, 2023). Studies have further confirmed that ICTs stimulate cognitive and innovative behavior but also streamlines processes which fosters the ability to process and share more information for decision-making (Kravchenko, 2021;Munir and Beh, 2019;Harju et al, 2023;Hussain et al, 2023). In the agriculture sector, basic ICTs like mobile phones and televisions have bridged the information gaps created by the inaccessibility of extension workers and prevalent costs associated with reaching out to official government outreach centres (Byamukama et al, 2022;Subramanian, Bozzola and Nugent, 2022;Ravindra et al, 2020).…”
Section: Smallholder Maize Farmers In Ugandamentioning
confidence: 99%
“…Previous studies associated the age at first regular digital device access with early digital device use experience by indicating that individuals who first regularly accessed digital devices earlier also enjoyed more frequent and richer early digital device use experiences, which emphasized the theoretical importance of the age at first regular digital device access in understanding early digital device use and its further impacts on individual development (van Deursen & van Dijk, 2011). Surveys have also indicated that a proportion of students first access digital devices later than others, mostly due to low family socioeconomic status or disadvantaged school conditions (Hussain et al, 2023). In this regard, research on the topic of age at first regular digital device access seeks evidence to promote educational equity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The desire for inclusivity within metaverse knowledge systems seamlessly aligns with the overarching societal objective of bridging digital disparities and championing equitable access to education and information. Notably, research conducted by Hussain et al (2023) underscores the concept of the "second-level digital divide," emphasizing disparities in individuals' online skills and usage trends. Addressing this divide assumes significant significance in the metaverse landscape, where participation should be uninhibited by factors such as socioeconomic status, geographical location, or technological infrastructure.…”
Section: Building Inclusive Metaverse Knowledge Systemsmentioning
confidence: 99%